DIFFERENCES IN EXPLOSIVE LEG POWER BETWEEN YOUNG CHILDREN WHO PLAY FOOTBALL AND THOSE WHO DO NOT - Živko Kalentić; Milan Cvetković; Jelena Obradović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Explosive leg power for soccer players represents one of the most important basic motoric abilities, coupled with speed and endurance. For this reason, it was interesting to compare young soccer players with other boys their age manifesting explosive leg power. The test sample contained 243 boys, 78 of which were soccer players, and 165 were not, aged 7-11 years from the city of Novi Sad. The differences in explosive leg power manifestation between children who played soccer and those who did not were explored by an independent T-test.